2016
DOI: 10.3390/molecules21040537
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Stem Cell Culture and Enrichment Using Poly(ε-Caprolactone) Scaffolds

Abstract: Abstract:The cancer stem cell (CSC) population displays self-renewal capabilities, resistance to conventional therapies, and a tendency to post-treatment recurrence. Increasing knowledge about CSCs' phenotype and functions is needed to investigate new therapeutic strategies against the CSC population. Here, poly(ε-caprolactone) (PCL), a biocompatible polymer free of toxic dye, has been used to fabricate scaffolds, solid structures suitable for 3D cancer cell culture. It has been reported that scaffold cell cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 27 publications
2
35
0
1
Order By: Relevance
“…Wang M, Cheng X, Zhu W, Holmes B, Keidar M, Zhang LG Tissue Eng Part A. 2014 Mar; 20(5-6):1060-71; G. Kumar, et al Freeform Fabricated Scaffolds with Roughened Struts that Enhance both Stem Cell Proliferation and Differentiation by Controlling Cell Shape, Biomaterials, 2012, 33 (16): 4022 -4030], it was shown that high surface roughness of scaffolds and wettability enhance osteogenic differentiation of hMSCs on scaffolds. With respect to reviewer comments, we described this issue more clearly and added more references, confirming that statement.…”
Section: Reviewer's Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang M, Cheng X, Zhu W, Holmes B, Keidar M, Zhang LG Tissue Eng Part A. 2014 Mar; 20(5-6):1060-71; G. Kumar, et al Freeform Fabricated Scaffolds with Roughened Struts that Enhance both Stem Cell Proliferation and Differentiation by Controlling Cell Shape, Biomaterials, 2012, 33 (16): 4022 -4030], it was shown that high surface roughness of scaffolds and wettability enhance osteogenic differentiation of hMSCs on scaffolds. With respect to reviewer comments, we described this issue more clearly and added more references, confirming that statement.…”
Section: Reviewer's Commentmentioning
confidence: 99%
“…The viability of hMSCs on scaffolds at 1 day of culturing was determined using a cell detachment protocol, described in [16]. The culture medium was removed with a micropipette.…”
Section: Cell Viability Analysis and Cell Growth On Scaffoldsmentioning
confidence: 99%
“…Over the course of time, researchers have tried to improve upon the existing protocol of sphere formation in order to make it more efficient, consistent, reliable and physiologically relevant. Various types of scaffolds consisting of chitosan-alginate, collagen, alginate and agarose have been used as 3D matrices to substitute low attachment plates [69][70][71][72]. In 2014, Cao et al generated tumorspheres from primary neuroblastoma cells driven from MYCN transgenic mice using a medium supplemented with fetal bovine serum (FBS) and β-mercaptoethanol.…”
Section: Floating Tumorspheresmentioning
confidence: 99%
“…In Causa et al (2006) authors described how a PCL scaffold, reinforced with hydroxyapatite (HA) particles, is a good solution for the regeneration of bones promoting the proliferation of human osteoblasts and for the regeneration of cartilage tissue (Wei et al, 2015;Zhang et al, 2016). Regarding new effective 3D cell culture applications, Palomeras et al (2016) used the PCL scaffolds for the in vitro growth of cancer stem cells (CSCs). These cell type represents a minor subpopulation in solid tumors able to drive tumor progression and metastatization.…”
Section: Introductionmentioning
confidence: 99%
“…These cell type represents a minor subpopulation in solid tumors able to drive tumor progression and metastatization. CSCs are difficult to culture in 2D systems and Palomeras et al (2016) successfully demonstrated their enrichment due to seeding them on a PCL scaffold. Their 3D PCL scaffolds resulted a useful way to enrich and propagate CSCs for further investigation targeted to this malignant subpopulation.…”
Section: Introductionmentioning
confidence: 99%